The Government’s Role for Facing the Fragmentation of Religious Authority in Da’wa Activity: Lessons Learned From Malaysia and Singapore - Rahman, Fazlul (Institut Agama Islam Syarifuddin Lumajang, 2023)
My previous research on Pandalungan Kiai as a mediatized world shows a complicated case of negotiation between Internet and religion. From mediatization perspective, we can see a clear dynamic interplay between Internet and Pandalungan Kiai as each of them try to influence one another. This interplay is actually the nature of a mediatization process which, furthermore, leads to an interesting phenomenon of the rhizomatic fragmentation of religious authority causing many uncontrolled Islamic discourses to emerge. As corollary to that phenomenon, this article questions the role of the state in controlling the religious diversity of its people and the emergence of various Islamic discourses to be able to give a proper response to the fragmentation. This current research dedicated to critically unpack the problem by focusing on the case of Malaysia and Singapore as each share similar socio-cultural life. The data collected through observation and interview with 22 informants consisted of imams, asatizs, scholars, and local civilians in Malaysia and Singapore during my research field work in November and December 2018. This study found that the two countries implemented a strict certification policy for religious leaders to regulate the diversity of religious life. This fact leads this article to conclude the importance of the role of the government in making strict rules for religious leaders to be able to face the various consequences of the rhizomatic fragmentation of religious authority caused by the coming of (new) media in da’wa activities.